Crystal structure of tetrakis (N-(2-hydroxyethyl)-N-isopropylcarbamodithioato-κS,S′)-(μ2(2-(pyridin-4-yl)vinyl)pyridine-κN,N′)dicadmium(II), C36H58Cd2N6O4S8 - Yeo, Chien Ing *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C36H58Cd2N6O4S8, monoclinic, P21/c (no. 14), a = 7.82927(4) Å, b = 11.64209(5) Å, c = 26.2493(1) Å, β = 95.6985(4)°, V = 2380.775(18) Å3, Z = 2, Rgt(F) = 0.0158, wRref(F2) = 0.0411, T = 100(2) K.